Correlates of Early-Stage Frailty—Sleep, Fitness, Oxidative Stress, and BMI - Netz, Yael; Ben-Zaken, Sigal; Zeev, Aviva; Dunsky, Ayelet (Frontiers in Medicine, 2021)
Frailty reflects a decreased reserve in multiple systems resulting from cumulative decline. Frailty markers should be identified as early as possible to attenuate the loss of reserve. The aim of this study was to identify potentially modifiable correlates of frailty in relatively healthy older adults. Volunteers (n=122) were recruited from local councils and, based on gender and age, were divided into one group of men aged 77.0 (±5.3), and two groups of women, aged 68.8 (±3.6) and aged 78.4 (±3.4). Frailty was assessed by a Frailty Index. The examined correlates were: physical activity, physical fitness (predicted peak VO2), sleep quality, oxidative stress (hydrogen peroxide – H2O2) and depression. Both groups of women had poor scores on physical fitness compared to women’s norms. In order to examine the contribution of each of the potential correlates to explaining the variance of frailty, stepwise regressions were performed for each group separately. Based on the results, none of the suggested correlates significantly explained the variability of frailty in the men. In the younger-aged women, predicted peak VO2 and sleep quality explained 22.4% of the variability of frailty. In the older women, Body Mass Index (BMI), oxidative stress and sleep quality explained 34.9% of the variance. It is possible that increased aerobic fitness and interventions for improving sleep quality in older, seemingly healthy women will slow down the frailty process. Further research is needed to assess potential correlates of frailty, and to initiate suitable interventions to mitigate the signs of frailty at an early stage.